Altered peri-seizure EEG microstate dynamics in patients with absence epilepsy - Liu, Hong; Tang, Haoling; Wei, Wei; Wang, Gesheng; Du, Yong; Ruan, Jianghai (Seizure (London, England), 2021)
•The inter-ictal EEG of AE patients differ from the resting-state EEG of healthy controls in microstates.•There exist altered EEG microstates dynamics from inter-ictal, pre-seizure to post-seizure states.•The EEG microstates of epileptic patients before and after absence seizure are characterized by a ‘slow down’ in transitions between microstates.•EEG microstates deepens our understanding on seizures, beyond the traditional EEG visual inspection. To investigate whether the parameters of EEG microstates changed before and after an absence seizure episode. AE patients with a current high frequency of seizures were included (n=21). Each included subject underwent a two-hour and 19-channel video EEG examination. Five epochs of 10-second EEG data in interictal, pre-seizure, and post-seizure states were collected from each AE patient. Five 10-second resting-state EEG epochs from sex- and age-matched HCs who reported no history of neurological or psychiatric disorders and visited the hospital for routine physical examinations were collected. Microstate analysis and source localization of microstates were performed using the LORETA KEY tool. Compared with the resting-state EEGs of HCs, the interictal EEGs of AE patients showed a higher relative transition rate from microstates B to D (p<0.05). From interictal to pre-seizure EEG, the total time ratio of microstate C and the occurrence of microstate B decreased significantly, while the duration of microstate B increased significantly (p<0.05). Compared with pre-seizure EEGs, microstate C in post-seizure EEGs showed a significantly downregulated total time percentage and occurrence (p<0.05). The source localization of each microstate in each condition also varied and showed spatial recovery tends from pre- to post-seizure states. Altered EEG microstate dynamics exist between inter-ictal EEGs of AE patients and resting-state EEGs of HCs and between pre- and post-seizure EEGs in AE patients. The EEG microstates of epileptic patients before and after absence seizures are characterized by a “slowdown” in transitions between microstates. Microstates might be used as an index to evaluate the temporal and spatial recovery process of absence seizures in AE.